OvisOme: atualização da base de dados de Ovis aries - Esteves, Eduardo (2021)
Databases are essential to store, annotate and provide the scientific community with all the information gathered by different omics studies, so that it can be used to understand the physio-pathological mechanisms underlying sheep diseases, as well as to develop new and improved diagnostic, prognostic and therapeutic strategies. OvisOme is a database that integrates the information produced by proteomics and studies that identify and quantify specific proteins in diseases of Ovis aries. When compared to other proteomics databases, the OvisOme stores and displays more information than other databases not specific for sheep, such as UniPro.